2015
DOI: 10.1016/j.jcin.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Comatose Cardiac Arrest Survivors With and Without ST-Segment Elevation Myocardial Infarction

Abstract: Early coronary angiography is associated with improved functional outcome among resuscitated patients with and without STEMI. Resuscitated patients with a presumed cardiac etiology appear to benefit from immediate coronary angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(147 citation statements)
references
References 25 publications
8
133
2
4
Order By: Relevance
“…Since the seminal observation by Spaulding et al, many studies have validated the role of angiography and PCI in survivors of OHCA with ST‐segment elevation on their postresuscitation ECG 6, 7, 8, 9, 10, 11, 12, 19. The positive results with the MRC protocol are most noticeable in the group without ST elevation because a well‐defined postarrest treatment pathway is lacking and early access to the CCL is controversial 9, 10. With an organized and coordinated approach, two thirds of patients gained early access to the CCL and almost 50% underwent coronary revascularization, which is significantly higher than previously reported at 33% 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the seminal observation by Spaulding et al, many studies have validated the role of angiography and PCI in survivors of OHCA with ST‐segment elevation on their postresuscitation ECG 6, 7, 8, 9, 10, 11, 12, 19. The positive results with the MRC protocol are most noticeable in the group without ST elevation because a well‐defined postarrest treatment pathway is lacking and early access to the CCL is controversial 9, 10. With an organized and coordinated approach, two thirds of patients gained early access to the CCL and almost 50% underwent coronary revascularization, which is significantly higher than previously reported at 33% 10…”
Section: Discussionmentioning
confidence: 99%
“…Coronary revascularization has been proven beneficial for patients with ST‐segment elevation myocardial infarction on their postarrest ECG 5, 6, 7, 8. However, it is clinically difficult to decide if and when to perform coronary angiography in patients resuscitated from OHCA who remain comatose and do not have a current consistent with injury on their postarrest ECG 4, 5, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…This preclinical, translational study shows such an approach is no better than when both cooling and reperfusion are delayed in a subject with an acute coronary occlusion. Cohort population studies of those without ST segment elevation post cardiac arrest have shown that at least one of every four such patients has an acutely occluded coronary (13)(14)(15)(16)(17). If immediate coronary angiography is not performed to find such occluded vessels, myocardium is lost and left ventricular function diminished.…”
Section: Discussionmentioning
confidence: 99%
“…In these resuscitated patients the lack of ST segment elevation does not rule out an acute coronary occlusion. Cohort studies have shown that approximately one in four post cardiac arrest patients without ST elevation has an acutely occluded coronary artery as the culprit for their out-of-hospital cardiac arrest (15)(16)(17). Currently, many interventional cardiologists are unsure how to best approach these patients (18), with some favoring treatment with immediate targeted temperature management, but delaying coronary angiography until evidence of favorable neurological recovery is seen.…”
Section: Current European Society Of Cardiology and American College Ofmentioning
confidence: 99%
“…24 The Interventional Council of the American College of Cardiology has just published an alternative approach recommending early coronary angiography for those post arrest without ST-segmentelevation, outlining unfavorable characteristics that could be considered before proceeding to the cath laboratory. 25 We have also published 2 cohort series from the International Cardiac Arrest Registry (INTCAR) Cardiology subgroup, 26,27 suggesting that early coronary angiography performed in postarrest patients without ST-segment-elevation does increase survival and favorable neurological outcome and that the angiographic findings in this patient subgroup may explain these results. We found in our series that one in 4 patients without ST-segment-elevation after cardiac arrest has an acutely occluded coronary at angiography.…”
Section: See Article By Waldo Et Al See Article By Geri Et Al See Artmentioning
confidence: 99%